A COMPARATIVE STUDY BETWEEN TOTALLY EXTRAPERITONEAL (TEP) AND TRANS ABDOMINAL PRE PERITONEAL (TAPP) LAPAROSCOPIC INGUINAL HERNIA REPAIR TECHNIQUES (Indian Journal of Applied-Basic Medical Sciences, 2020)
Objective: The study was undertaken to compare the efficacy, safety and patient satisfaction between the two techniques of laparoscopic inguinal hernia repair. Methodology: This was a comparative study carried out at a tertiary care hospital from August 2017 to July 2019. Diagnosis of inguinal hernia was made based on history and clinical examination and ultrasound scan of the abdomen. 50 patients enrolled in the study for laparoscopic hernia repair were equally divided into 2 groups, Group A - TEP group and Group B - TAPP group. Results: The outcomes were compared between both groups. The mean operative time required for TEP was 68 minutes and that for TAPP was 81 minutes. No major complications were noted in either TEP group or TAPP group .Minor complication rate was 28 % for Laparoscopic TEP group and 24 % for Laparoscopic TAPP group. The hospital stay in TEP was (2.36 ± 1.43) & that of TAPP was (2.32± 1.47), so it was statistically not significant. Conclusion: Laparoscopic repair of inguinal hernia has a prolonged learning curve but once mastered it can be done with decreased operative time, early post operative recovery and faster return to work. TEP and TAPP both are methods of choice for Laparoscopic inguinal hernia repair and it is difficult to establish the superiority of one over the other. Choice between TEP and TAPP depends on the preference and proficiency of the individual surgeon.
Keywords: mesh repair; minimal access surgery; post operative pain; patient; satisfaction